A study of atmospheric mixing of trace gases by aerial sampling with a multi-rotor drone. (July 2018) - Chang, Chih-Chung; Chang, Chih-Yuan; Wang, Jia-Lin; Lin, Ming-Ren; Ou-Yang, Chang-Feng; Pan, Hsiang-Hsu; Chen, Yen-Chen
Abstract: We exploited a novel sampling vehicle, a multi-rotor drone carrying a remote-controlled whole air sampling device, to collect aerial samples with high sample integrity and preservation conditions. An array of 106 volatile organic compounds (VOCs), CO, CH4, and CO2 were analyzed and compared between the aerial samples (300-m height) and the ground-level samples in pairs to inspect for vertical mixing of the trace gases at a coastal site under three different meteorological conditions of local circulation, frontal passage, and high-pressure peripheral circulation. A rather homogeneous composition was observed for the sample pairs immediately after the frontal passage, indicating a well-mixed condition below 300 m. In contrast, inhomogeneous mixing was observed for the sample pairs under the other two conditions (local circulation and high-pressure peripheral circulation), suggesting different layers of air masses. Furthermore, information of unique source markers, composition profiles, and lifetimes of compounds were used to differentiate the origins of the air masses aloft and at the surface to substantiate the observed inhomogeneity. The study demonstrates that, with the availability of the near-surface aerial sampling coupling with in-laboratory analysis, detailed compositions of trace gases can now be readily obtained with superior data quality. Based on the distinctive chemical compositions, the sources, transport, and atmospheric mixing of the airborne pollutants in the near-surface atmosphere can be better studied and understood. Graphical abstract: Image 1 Highlights: Aerial whole air sampling can be easily performed with a multicopter drone. Air mixing was studied by vertical sampling up to 300 m. A large array of trace gases were exploited to form distinctive compositions. Source and transport of air masses were deduced from chemical compositions.